2011
DOI: 10.3109/08880018.2011.562601
|View full text |Cite
|
Sign up to set email alerts
|

Second Malignant Neoplasms Following Childhood Cancer: A Study of a Recent Cohort (1987–2004) from the Childhood Cancer Registry of The Rhône-Alpes Region (ARCERRA) in France

Abstract: Studies of second malignant neoplasms (SMNs) in childhood are generally conducted in old cohorts. The aim of this study was to determine the actual incidence of all SMNs in a recent cohort. The authors studied a cohort of 2907 children included in the population-based Childhood Cancer Registry of the Rhône-Alpes Region for a first cancer diagnosed between 1987 and 2004. Total follow-up was 22,722 person-years, with a median follow-up of 9.8 years (range, 00.0-22.8 years). Fifty-four SMNs were reported in 52 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…Improved survival of these patients, from 25% in the 1970s to 75% in 2000, suggests that about one French person in 850 has survived childhood cancer [2,3] and that management of treatment, including chemotherapy, surgery, and/or irradiation, and healthcare support services of these patients has greatly improved [4]. Nevertheless, long-term effects of disease and sometimes heavy treatment can include disabilities or even secondary cancers that lead to death [5][6][7][8][9][10][11]. Carcinogenic or not, iatrogenic effects affect about two-thirds of survivors [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved survival of these patients, from 25% in the 1970s to 75% in 2000, suggests that about one French person in 850 has survived childhood cancer [2,3] and that management of treatment, including chemotherapy, surgery, and/or irradiation, and healthcare support services of these patients has greatly improved [4]. Nevertheless, long-term effects of disease and sometimes heavy treatment can include disabilities or even secondary cancers that lead to death [5][6][7][8][9][10][11]. Carcinogenic or not, iatrogenic effects affect about two-thirds of survivors [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, long-term effects of disease and sometimes heavy treatment can include disabilities or even secondary cancers that lead to death [5][6][7][8][9][10][11]. Carcinogenic or not, iatrogenic effects affect about two-thirds of survivors [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the latency period is long, and studies from the CCSS and the British CCSS cohorts showed a median time to occurrence around 19–20 years after treatment of the first primary cancer [32, 85]. In some studies, the reported shorter latency periods could be in part attributed to the incorporation of routine ultrasound screening in at-risk cancer survivors [86, 89]. …”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…1). Thyroid cancer, specifically papillary thyroid carcinoma (PTC), is one of the most frequently diagnosed subsequent primary malignancies in childhood cancer survivors [28, 85, 86]. Survivors of childhood Hodgkin disease, for example, are 18.3-fold more likely to develop PTC [26], although benign thyroid nodules are still more common [31].…”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…Median latency between first and second cancers in our study was shorter than that in the Childhood Cancer Survivor Study (CCSS) cohort (5 years versus 11.7 years), but the CCSS does not take into account early leukemias arising less than 5 years after the first cancer. This was partially attributable to the shorter latency of our secondary leukemias (3 year and 5 months versus 7.1 years) (12). However, Rihani et al also noted a shorter latency at 3 years for secondary acute myeloblastic leukemias (13) Carcinogenesis is a complex process and can develop as a result of many factors.…”
Section: Discussionmentioning
confidence: 84%